Analgesic efficacy of intra-articular morphine after arthroscopic knee surgery in sport injury patients - Yari, Mitra (Kermanshah University of Medical Sciences, 2013)
BACKGROUND: Anterior Cruciate Ligament (ACL) tearing is a common injury among football players. The present study aims to determine the best single-dose of intra-articular morphine for pain relief after arthroscopic knee surgery that, in addition to adequate and long-term analgesia, leads to fewer systemic side effects. METHODS: This clinical trial was conducted on 40 ASA-I athletes. After surgery, all participants received an injection of 20cc of 0.5% intra-articular bupivacaine. In addition, the first control group received a saline injection and 5, 10 and 15 mg of morphine were respectively injected into the joints of the second, third and fourth groups by use of Arthroscopic equipment before the Arthroscopic removal. The amount of pain based on VAS at 1, 2, 4, 6 and 24 hours after surgery, duration of analgesia and the consumption of narcotic drugs were recorded. RESULTS: The VAS scores in the fourth, sixth and twenty-fourth hours after surgery showed a significant difference between the study groups. The average time to the first analgesic request from the bupivacaine plus 15 mg morphine group was significantly longer than other groups and total analgesic requests were significantly lower than other groups. No drowsiness complications were observed in any of the groups in the first 24 hours after injection. CONCLUSIONS: Application of 15 mg intra-articular morphine after Arthroscopic knee surgery increases the analgesia level as well as its duration (IRCT138902172946N3).